2008
DOI: 10.1103/physrevb.78.035321
|View full text |Cite
|
Sign up to set email alerts
|

Homoepitaxial growth of Bi(111)

Abstract: Homoepitaxial growth of Bi͑111͒ at temperatures between 80-300 K has been studied using spot profile analyzing low-energy electron diffraction ͑SPA-LEED͒ and scanning tunneling microscopy ͑STM͒. From the intensity oscillations of the ͑00͒-spot with Bi coverage and the STM topography of two-dimensional ͑2D͒ islands at low coverage, a pure 2D nucleation followed by a quasi bilayer-by-bilayer growth mode has been confirmed. The oscillation amplitude decays slowly with coverage, indicating a slow kinetic roughenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
(53 reference statements)
0
17
2
Order By: Relevance
“…Brune et al 22 found a value of 0.157 eV for Ag on Pt͑111͒, while in the case of Bi on Bi͑111͒ it is 0.135 eV. 8 Additionally, the shape transition occurred in our case is far from the nucleation regime, i.e., at the steady-state regime, which was not the case for Ag/Pt͑111͒, where the shape transition was found just above the nucleation regime.…”
contrasting
confidence: 49%
See 3 more Smart Citations
“…Brune et al 22 found a value of 0.157 eV for Ag on Pt͑111͒, while in the case of Bi on Bi͑111͒ it is 0.135 eV. 8 Additionally, the shape transition occurred in our case is far from the nucleation regime, i.e., at the steady-state regime, which was not the case for Ag/Pt͑111͒, where the shape transition was found just above the nucleation regime.…”
contrasting
confidence: 49%
“…The coverage regime we have studied is far below the coalescence regime, since a previous study exhibited no coalescence at 0.5 BL coverage. 8 Thus, the second assumption also holds true. According to Eq.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, the growth is not purely SK, and is thus often referred to in the literature as being a quasi bilayer-by-bilayer mode, such as in Refs. [20,49].…”
Section: Discussionmentioning
confidence: 99%